The ultra-flexible films of super conductive carbon black/poly(vinylidene fluoride) as electrothermal materials. (25th September 2019) - Wang, Yating; Xie, Jiong; Wang, Xinlong
Abstract: The electrothermal films of super conductive carbon black/poly(vinylidene fluoride) (PVDF/SCB) were fabricated via solution-blending method. The TEM showed that SCB had the unique branched string bead-like structure. The heating performances of the electrothermal films with SCB content or under different voltages have been studied and the results showed that the prepared films have good electric heating performances and operational stability. Besides, the elongation at break for the films was above 300%, which indicated the films had the excellent flexibility.